Islamic Educational Approaches to the Resilience of Former Terrorism Convicts: A Study of the Social Reconstruction Curriculum - Asrori; Masudi, Muhammad Maulana; Shafwan, Muhammad Hambal (LETIGES, 2026)
This study examines Islamic Educational Approaches to the Resilience of Former Terrorism Convicts through an analysis of the Social Reconstruction Curriculum developed and implemented by the Lingkar Perdamaian Foundation (Yayasan Lingkar Perdamaian/YLP) in Lamongan, East Java. The study aims to explain how Islamic education contributes to building resilience among former terrorism convicts, particularly in fostering ideological transformation, psychosocial recovery, and sustainable social reintegration. This study employed a descriptive qualitative approach and collected data through in-depth interviews, participant observation, and document analysis involving former terrorism convicts, programme facilitators, and institutional administrators. The researchers conducted data analysis using thematic analysis, drawing on social reconstruction curriculum theory and social-ecological resilience theory. The findings indicate that YLP's Social Reconstruction Curriculum integrates religious moderation education, Sufi-based spiritual approaches and the Living Qur'an method, skills training and economic empowerment, peace campaigns, and structured family and community reintegration. This holistic and dialogical Islamic educational approach has proven effective in strengthening psychosocial resilience, reconstructing religious and social identities, and facilitating disengagement from violent extremist ideologies. The study underscores that deradicalisation grounded in Islamic education constitutes a long-term, humanistic, and contextual process of social reconstruction, and it offers an alternative curriculum model to strengthen deradicalisation programs and post-conflict peacebuilding initiatives in Indonesia.